The use of an Edge Load Profile static bench for the qualification of alpine skis - Petrone, N. (Procedia Engineering, 2012)
The work reports the results of several tests performed on a set of commercial skis ranging from racing to recreational skis by means of a special bench designed for evaluating the Edge Load Profile produced by a ski when pressed against a bed of calibrated load cells. The test bench is equipped with 21 uniaxial load cells of 100 mm width and with a linear actuator able to press any type of alpine ski at edging angles ranging from 0¡ to +/- 70¡. The Edge Load Profiles were presented along a normalized ski length and their shapes were compared within each category of skis. The bench output was clearly revealing the presence of critical spots along the ski where either the contact to the ground was missing or some non-uniform peaks were present. The experiences here presented confirm the appropriateness of the Edge Load Profile bench as tool for the skis qualification process and its continuous design improvement.